A minimum income guarantee in India: Social assistance for a post-pandemic world - Santosh K. Mehrotra; Anjana Rajagopalan; Rakesh Ranjan Kumar (University of Bath, Centre for Development Studies (CDS), 2022)
Amidst the bleak picture of increasing joblessness and indebtedness presented by employment surveys and debt surveys, a minimum standard of living for India's poor seems to be under threat. The sudden exogenous shock of COVID-19 to the incomes of the poor has made the case of a minimum income guarantee (MIG) for the poor more urgent. Rather than adopting a quasi-UBI and doing away with many existing developmental programmes, this paper makes a case for, and presents the design of a better strategy of cash transfers as a supplement to income from livelihoods, keeping fiscal considerations in mind. Had it already been in place by early 2020, it would only have required a ramping up of transfers to protect the incomes of the poor. This paper focuses on feasible pathways for ensuring equity, recognising the importance of addressing the issues of social justice, and reduction of vulnerabilities. Thus, the stress is on technical and economic aspects of such a programme. Essentially, the paper focuses on identifying vulnerable populations to be targeted for efficient and just transfer.
Keywords: 330; Universal Basic Income; Conditional Cash Transfer; Minimum Income Guarantee